A Success of Some Sort: Social Enterprises and Drip Irrigation in the Developing World. (March 2016) - Venot, Jean-Philippe
Highlights: The promises and potential of smallholder drip irrigation are discursive constructs. Drip irrigation is appealing because of its association to social entrepreneurship. Social entrepreneurship is not an alternative development model as is often claimed. Smallholder drip irrigation is an artifact of agricultural development projects. Drip irrigation will not transform smallholder farming in sub-Saharan Africa. Critical engagement with narratives can lead to renewing development practice. Summary: This paper explains the processes behind the framing of drip irrigation as a promising technology to address current poverty and environmental challenges in the developing world. I draw from critical development and science and technology studies and highlight that this imagery has been actively performed. Insiders elaborated a compelling narrative calling upon a will to improve through technology and the moral legitimacy of social entrepreneurship in development; they worked hard to establish a supportive coalition in an ever wider network. This story hinges on several assumptions, which upon closer scrutiny appear to be problematic: the unicity of smallholder farming, the attribution of inherent technical characteristics to a specific object—the "drip kit"—regardless of the context in which it is used, and the framing of social entrepreneurship and market-based approaches as alternative models even though these rather constitute a re-working of existing arrangements within the international development community. Nonetheless, the pro-poor and environmentally friendly smallholder drip irrigation narrative still continues to be successful in harnessing the support of the international development community, despite the little capacity drip irrigation has had to transform smallholder farming, especially in sub-Saharan Africa. Unpacking the origins, actors, and building blocks of the discursive success of smallholder drip irrigation provides fresh perspectives on the practices of development in the sector and is the first step toward more meaningful engagement with smallholder farmers in the developing world.